2020
DOI: 10.1186/s12871-020-00975-2
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction by SOFA score in ICU-patients after cardiac surgery; comparison with traditional prognostic–models

Abstract: Background: There are many prognostic models and scoring systems in use to predict mortality in ICU patients. The only general ICU scoring system developed and validated for patients after cardiac surgery is the APACHE-IV model. This is, however, a labor-intensive scoring system requiring a lot of data and could therefore be prone to error. The SOFA score on the other hand is a simpler system, has been widely used in ICUs and could be a good alternative. The goal of the study was to compare the SOFA score with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 24 publications
5
32
0
Order By: Relevance
“…The more serious the illness is, the higher the score is. Studies have shown that the severity of the disease is closely related to the risk of delirium [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The more serious the illness is, the higher the score is. Studies have shown that the severity of the disease is closely related to the risk of delirium [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A higher score infers aggravating conditions in the patients. Although SOFA was not initially designed to predict mortality, several studies revealed that the SOFA score could predict morbidity and mortality and this specific application has been validated in severely ill patients [ [9] , [10] , [11] , [12] , [13] ].Therefore, it is of interest to determine whether the SOFA score could predict mortality in the COVID-19 population.…”
Section: Introductionmentioning
confidence: 99%
“…The more serious the illness is, the higher the score is. Studies have shown that the severity of the disease is closely related to the risk of delirium 18,19 .…”
Section: The Aim and Designmentioning
confidence: 99%